(untitled) (AL-FIKRAH: Jurnal Kajian Islam, 2025)
The practice of agricultural profit-sharing has been practiced for generations, but there are no detailed rules for carrying out the agreement in accordance with Islamic law, which sometimes causes problems related to the distribution mechanism of agricultural products that have been carried out. This study aims to determine the profit-sharing system between landowners and workers regarding community income in Massewae Village, Duampanua District, Pinrang Regency and how the Islamic jurisprudence (fiqh muamalah) reviews this profit-sharing system. This study uses qualitative research in the form of field research using data collection methods based on observation, interviews, and documentation. The data analysis technique used in this study refers to the concept of an interactive model. The results of this study indicate several things. First, the profit-sharing system for the red corn agricultural sector in Massewae Village, Duampanua District, Pinrang Regency uses a three-part system with the condition that the first to third harvests are given to the land cultivators. The fourth harvest is divided between the landowner and the cultivators after all debts are paid off. Second, the practice of agricultural profit-sharing in Massewae Village, Duampanua District, Pinrang Regency, cannot yet be fully used as a model because certain contractual requirements in Islamic jurisprudence have not been met. The implications of this research are expected to serve as a reference for academics working in Islamic law, a guideline for institutions focusing on profit-sharing systems, and a resource for students seeking to delve deeper into profit-sharing.